Silesia – issues of language and ethnicity in the long 16th century - Lipiński, Cezary (Wydawnictwo eBooki.com.pl, 2014)
The primary issue considered in this paper is the question to what extent Silesia in the long 16th century can be considered a region cohesive in the ethnical and linguistic context. Available research materials indicate deepening bilingual tendencies in the region, however the extent of each of the languages and ethnic groups are impossible to adequately asses due to constant changes in the demographical situation of Silesia, changes brought about by various factors, including economic and political. It is true that humanism formed an integrating factor, which led to the formation of local patriotism. Due to this phenomenon there came to be a belief in the existence of „Silesian Nation” as well as the need to look for a factor binding the population together, something extending beyond the ius soli principle. Seeing as both „the love of Motherland – Silesia” and the spreading of the idea of the Silesian Nation were both constructs of groups of humanists and scholars, the first important bridge with the symbolical culture was Latin, quickly replaced by the solidified German-language culture. It dominated lay culture at the end of the 16th and beginning of the 17th century, paving the way for development in the following centuries.
Keywords: national minorities; multiculturalism; ethnic structure; languages; cultural diversity